Dinâmica e os estoques de carbono na Floresta Tropical Atlântica - Brasil - Thiago Igor Ferreira Metzker (2012)
Carbon is the fourth most abundant element on the planet. Considering only the Amazon Rainforest, it is estimated that carbon stocks present in all forest compartments are around 100 billion tons, which is equivalent to more than 10 years of all global fossil fuel emissions (Malhi et al., 2006; Davidson et al., 2012). As a result, changes in forest carbon stocks, due to change in landscape use, have significant impacts on global climate change (Kelling; Phillips, 2007).